Immersed in the realm of possibility: An encounter with digital technologies in early childhood education? - Stojković, Jelena (Studies in Teaching and Education, 2025)
In a world involving many, education can be understood as an encounter that presupposes their repositioning and overcoming of various binaries (such as nature-culture, real-virtual, adult-child, and others) that reflect and support power relations where the first in a dyad has power/dominance over the other. In this context, understanding education as a humanizing practice needs to be deconstructed and deterritorialized. Starting from the question of what and whom we are educating in the moment we live in, thinking with different posthumanist and poststructuralist ideas and concepts as lines of liberation, and examples of encounters with digital technologies, and many around and beyond them, this paper aims to explore the contours of preschool education that fall outside predefined (humanistic) frameworks, and to point to digital micro-moments in and outside the early childhood center, which remain overshadowed by dominant understandings and practices constructed by adults (particularly researchers). Such reflections with (beings, processes, objects, ideas...) indicate the need to recognize and appreciate unpredictability as a value in the educational process, to develop the capacity for joint action, and to move the use of digital technologies out of frameworks that assume their understanding as tools subordinated to human purpose, thereby excluding other materialities, rather than being inseparably intertwined with them.
Keywords: posthumanism; poststructuralism; early childhood education; digital technologies; ChatGPT